An inventory of the names of vascular plants endemic to Italy, their loci classici and types - Peruzzi, Lorenzo; Domina, Gianniantonio; Bartolucci, Fabrizio; Galasso, Gabriele; Peccenini, Simonetta; Raimondo, Francesco M.; Albano, Antonella; Alessandrini, Alessandro; Banfi, Enrico; Barberis, Giuseppina; Bernardo, Liliana; Bovio, Maurizio; et al. (Phytotaxa, 2015)
The census of the loci classici of 1,400 Italian endemic vascular plants (i.e. not thriving elsewhere with the exception of Corsica and Malta) is here presented and described. The effective place of publication of accepted names, basionyms and homotypic synonyms were identified and critically verified. This often resulted in some change in authorship attribution and, in seven cases, in validation problems (Asperula cynanchica var. lactea var. nov., A. lactea comb. nov., Biscutella laevigata subsp. raffaelliana subsp. nov., Ferulago nodosa subsp. geniculata comb. & stat. nov., Limonium tineoi comb. nov., L. usticanum sp. nov., Noccaea torreana comb. nov.). The geographic information on the loci classici was excerpted from the protologues, as well as information on typification for the taxa described before 1 January 1958. The names without holotype are 796. For 347 names a lecto- or neo-typification is available in literature, while 449 currently accepted taxa still need of type designation.